THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE: Study on PMA South Korea PT. Hilon Surabaya - Mochklas, Mochamad (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The purpose of this study is to find out how much influence leadership style, organizational culture and work motivation have on employee performance, especially employees in the production division at PMA PT. Hilon Surabaya. Simultaneously and partially leadership style, organizational culture and work motivation have a significant effect on employee performance. Leadership style has a dominant influence on employee performance of 0.382 while work motivation of 0.156 is the smallest coefficient value in this study, however employee motivation is still needed to improve employee performance. The results of this study are expected to be a source of information to review human resource management policies, especially in relation to leadership style, organizational culture, work motivation and employee performance.